The corporate diversity jigsaw - Kamalnath, Akshaya, 1987- (Cambridge : Cambridge University Press, 2023)
Although diversity in companies is a topic of great interest, significant aspects of the issue are often left out of the debate. The Corporate Diversity Jigsaw connects all the dots so that steps taken to address issues of diversity in business organisations can be more effective. Akshaya Kamalnath offers a nuanced justification of exactly what types of diversity are most useful for corporations, where they should be implemented, and how best to address diversity in ways that account for recent social movements such as #MeToo and Black Lives Matter. After a critical assessment of quotas and disclosure requirements across jurisdictions, she provides a different way to solve the problem, by encouraging companies to make improvements to their culture and internal processes. This timely book offers a balanced analysis, practical solutions, and fresh perspectives on how corporate culture and social movements impact diversity efforts.
Defining diversity -- Corporate governance and diversity -- Social movements and diversity -- Legal and market initiatives -- Corporate culture -- A proposal to reconcile corporate law with diversity and other societal issues -- Conclusion.
Title from publisher's bibliographic system (viewed on 12 Dec 2022).
Keywords: Corporation law -- Social aspects; Social responsibility of business -- Law and legislation